1995
DOI: 10.1901/jeab.1995.63-331
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Differing Response‐force Requirements on Fixed‐ratio Responding of Rats

Abstract: Rats were exposed to two-component multiple schedules of food delivery. In the first experiment, 15 responses were required to produce food in both components. A downward force of 0.25 N (25 g) was always required to operate the response lever in one component. In the other, the required force was 0.25, 0.50, 1.00, or 2.00 N (25, 50, 100, or 200 g). In the second experiment, 0.25 N of force operated the lever in one component, but in the other, the force requirement for five consecutive responses at the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
2
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 40 publications
4
40
2
5
Order By: Relevance
“…These results are consistent with the findings of Alling and Poling (1995), who found that increased response effort decreases response rates and increases postreinforcement pauses. For 4 out of5 of the rats, the relationship between self-control and response latency was statistically significant, as were the combined data for all of the rats.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with the findings of Alling and Poling (1995), who found that increased response effort decreases response rates and increases postreinforcement pauses. For 4 out of5 of the rats, the relationship between self-control and response latency was statistically significant, as were the combined data for all of the rats.…”
Section: Discussionsupporting
confidence: 92%
“…Note that at the 2-g force requirement, threshold and criterion were equal (only open circles). In previous studies not using force transducer methods only criterion response rates were recorded (e.g., Alling & Poling, 1995) and compared across force requirements. However, once the force requirement has been changed, the defined operant has also been changed.…”
Section: Resultsmentioning
confidence: 99%
“…Time and effort are two basic dimensions of all observable behavior, but while the temporal dimensions of behavior have been measured extensively, the effort dimension has received little attention (Alling & Poling, 1995;Fowler, 1987). However, more recent work has described an apparatus and procedure for quantifying response effort in CD-1 mice (Zarcone, Chen, & Fowler, 2007).…”
mentioning
confidence: 99%
“…The presence of an interaction suggests that response-force changes do not function simply as changes in response requirement (i.e., they do not simply change bias). An alternative explanation, suggested by Alling and Poling (1995), might be that increases in response force or response effort function as aversive events and reduce the value of the schedule of reinforcement. If the increases in force are thought of as punishing responding in some way, then they might be best regarded as subtracting from the effective reinforcement rates.…”
Section: Discussionmentioning
confidence: 99%